2024
DOI: 10.3389/fcimb.2024.1279218
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between the gut microbiota and insomnia: a two-sample Mendelian randomization study

Qianfei Wang,
Tianci Gao,
Weichao Zhang
et al.

Abstract: BackgroundChanges in the gut microbiota are closely related to insomnia, but the causal relationship between them is not yet clear.ObjectiveTo clarify the relationship between the gut microbiota and insomnia and provide genetic evidence for them, we conducted a two-sample Mendelian randomization study.MethodsWe used a Mendelian randomized two-way validation method to discuss the causal relationship. First, we downloaded the data of 462,341 participants relating to insomnia, and the data of 18,340 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Notably, a previous study found that depletion of the gut microbiota by antibiotics significantly affects sleep/wake behavior, potentially through disruptions in neurotransmitter balances, such as serotonin, underscoring the microbiome’s regulatory capacity on sleep ( Ogawa et al., 2020 ). Additionally, a more recent study proposes a causal link between specific gut microbiotas and insomnia via a Mendelian randomized two-way validation method ( Wang et al., 2024 ). These findings highlight the complexity of the gut-brain axis and its implications for sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a previous study found that depletion of the gut microbiota by antibiotics significantly affects sleep/wake behavior, potentially through disruptions in neurotransmitter balances, such as serotonin, underscoring the microbiome’s regulatory capacity on sleep ( Ogawa et al., 2020 ). Additionally, a more recent study proposes a causal link between specific gut microbiotas and insomnia via a Mendelian randomized two-way validation method ( Wang et al., 2024 ). These findings highlight the complexity of the gut-brain axis and its implications for sleep disorders.…”
Section: Discussionmentioning
confidence: 99%